Recrystallization of Iron Materials Under The Influence of High-Temperature Heat Treatment: A Molecular Dynamics Study - Janga Hauwali, Nikodemus Umbu; Setyawan Bani, Marsi Devid; Supu, Amiruddin; Arkundato, Artoto (Universitas Jember, 2024)
Simulations have been carried out to study the recrystallization of iron materials after heat treatment. The heat treatment carried out consists of heating the iron from room tempera-ture to critical temperature with different heating temperatures and cooling to room tem-perature with different cooling times. This study was carried out to obtain information on the occurrence of material recrystallization after the heat treatment process was carried out. This simulation approach was carried out using molecular dynamics methods and utilizing LAMMPS software. The heat treatment process begins by heating the iron from room temperature (300 K) until it reaches a critical temperature, even past the critical temperature value. Then a cooling process is carried out to observe the material recrystallization process. Through these two stages of heat treatment, analysis is carried out to observe the material structure at the end of the simulation. Based on the simulations that have been carried out, the results show that the ma-terial’s recrystallization is more influenced by the cooling time than the initial cooling tem-perature. More than 60% of the BCC structures formed at the end of the simulation for all initial cooling temperatures, but for very short cooling times 16% of the BCC.